1997
DOI: 10.1111/j.1439-0434.1997.tb00339.x
|View full text |Cite
|
Sign up to set email alerts
|

The Symptoms and Cause of Guava Wilt in South Africa

Abstract: Wilt of guava (Psidium guajava), a serious disease occurring in most guava producing areas of the Northern and Mpumalanga provinces of South Africa, was shown to be induced by a fungus tentatively identified as Penicillium vermoesenii. This fungus is the cause of a blight of ornamental palms in the United States and Belgium and its occurrence on guava is enigmatic. Pathogenicity tests were conducted in the glasshouse and under field conditions. Symptoms on trees include wilting, chlorosis and defoliation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…are highly effective/virulent and has the ability to infect the plant successfully and causes histopathological changes very efficiently. In the infection process some important steps are common for all strategies including adhesion and penetration to the surface of the plant and absortion of required nutrients from the plant cells (Dwivedi 1991;Hardham, 2001;Schoeman et. al., 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…are highly effective/virulent and has the ability to infect the plant successfully and causes histopathological changes very efficiently. In the infection process some important steps are common for all strategies including adhesion and penetration to the surface of the plant and absortion of required nutrients from the plant cells (Dwivedi 1991;Hardham, 2001;Schoeman et. al., 1997).…”
Section: Resultsmentioning
confidence: 99%
“…A survey on nematode and wilt problem of guava was carried out in Allahabad region and its adjacent areas in U.P., India (Ruchi et al, 2002). Wilted guava plants have also been reported from South Africa (Grech, 1985;Schoeman et al, 1997), Brazil (Junqueira et al, 2001), Pakistan (Ansar et al, 1994), Bangladesh (Hamiduzzaman et al, 1997), and Canberra, Australia (Lim and Manicom, 2003). In this article, an interaction process by Fusarium oxysporum and Fusarium solani was studied by scanning electron microscopy (SEM) to understand the penetration and establishment of infection in guava root.…”
Section: Introductionmentioning
confidence: 95%
“…During rapid decline, leaves tend to shrivel and die on the trees, which assume a scorched appearance. When decline occurs more slowly, leaves drop gradually, resulting in complete defoliation (Schoeman et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Diseased plants show symptoms of chlorosis, defoliation, wilt and eventually die (Kurosawa, ; Hsieh et al ., ; Leu et al ., ). Wilt disease has also been reported to cause serious losses of guava in tropical and subtropical countries such as Malaysia (Schoeman, ), South Africa (Schoeman et al ., ) and Thailand (Athipunyakom & Luangsa‐ard, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have investigated the aetiology and ecology of guava wilt (Kurosawa, ; Leu & Kao, ; Schoeman et al ., ; Lim & Manicom, ), the mechanism of infection of guava plants by the pathogen in the field remains controversial. Several reports (Kurosawa, ; Lim & Manicom, ) showed that the artificial inoculation of N .…”
Section: Introductionmentioning
confidence: 99%